DUKUNGAN KELUARGA TERHADAP KUALITAS HIDUP PASIEN SYSTEMIC LUPUS ERYTHEMATOSUS (SLE) DI RSUPN DR. CIPTO MANGUNKUSUMO - Rosi Damayati; Zakiyah; Nuniek Setyo Wardani (Jurnal Kesehatan dan Pembangunan, 2023)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disorder that can cause inflammation and damage to the skin, joints, tissues and organ systems of the body which can be caused by multifactors. WHO records the number of people with lupus in the world to date has reached five million people, and each year more than 100 thousand new cases are found. The high mortality rate due to lupus needs special attention because around 550 people died from lupus in 2016. The purpose of this study was to determine the relationship of family support to the quality of life of patients with Systemic Lupus Erythematosus (SLE) in Dr. Cipto Mangunkusumo. This study used a cross-sectional approach and bivariate analysis using the Chi Square test. The results of the study of 64 respondents showed that family support had a significant relationship with the quality of life of patients with Systemic Lupus Erythematosus (SLE), with a p-value of 0.027. The results of this study indicate that there is a significant relationship between family support and the quality of life of SLE patients